A Nanocellulose Polypyrrole Composite Based on Tunicate Cellulose - Dawei Zhang; Qing Zhang; Xin Gao; Guangzhe Piao (International Journal of Polymer Science)
The water-dispersed conductive polypyrrole (PPy) was prepared via the in situ oxidative chemical polymerization by using ammonium persulfate (APS) as oxidant and tunicate cellulose nanocrystals (T-CNs) as a dopant and template for tuning the morphologies of PPy nanoparticles. Highly flexible paper-like materials of PPy/T-CNs nanocomposites with high electrical conductivity values and good mechanical properties were prepared. The structure of nanocomposites of PPy/T-CNs was investigated by using Fourier transform infrared spectroscopy. Scanning electron microscopy and transmission electron microscopy analyses of the composites revealed that PPy consisted of nanoparticles about 2.5 nm in mean size to form a continuous coating covered on the T-CNs. The diameters of the PPy nanoparticles increased from 10 to 100 nm with the increasing pyrrole amount. Moreover, electrical properties of the obtained PPy/T-CNs films were studied using standard four-probe technique and the electrical conductivity could be as high as 10−3 S/cm.